The Industrial History in Urban Imaginaries and City Images: A Comparison between Dortmund and Glasgow. - Richter, Ralph (Lit, 2020)
This paper presents results of a research project carried out between 2011 and 2014 at the University of Technology in Darmstadt, Germany. Under the title "City Marketing and the Intrinsic Logic of Cities" a team of researchers investigated the professional image production in city marketing agencies and took this as an inroad to better understand city-specific patterns of social order, meanings and beliefs. While the focus of the research originally was an the "intrinsic logic of cities", a particular aspect attracted our attention. We became aware that the industrial heritage plays - both physically as well as symbolically - an entirely different role in Dortmund and Glasgow. This was an interesting observation, since both cities have a comparable industrial history. Both were important centers of steel production and heavy industry, both experienced a strong labor migration and a strong urbanization, both were centers of the labor movement and both were faced with long-standing deindustrialization, economic and physical decline and Population loss.
Keywords: Stadtmarketing; Stadtbild; Industriestadt; Strukturwandel; Imagepflege; Kulturerbe; Standortmarketing; Städtevergleich; Vergleichsuntersuchung